2020
DOI: 10.3390/ph13090233
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selective Growth-Inhibitory Activities of Phytochemicals, Synthetic Phytochemical Analogs, and Antibiotics against Diarrheagenic/Probiotic Bacteria and Cancer/Normal Intestinal Cells

Abstract: A desirable attribute of novel antimicrobial agents for bacterial diarrhea is decreased toxicity toward host intestinal microbiota. In addition, gut dysbiosis is associated with an increased risk of developing intestinal cancer. In this study, the selective growth-inhibitory activities of ten phytochemicals and their synthetic analogs (berberine, bismuth subsalicylate, ferron, 8-hydroxyquinoline, chloroxine, nitroxoline, salicylic acid, sanguinarine, tannic acid, and zinc pyrithione), as well as those of six c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
(53 reference statements)
4
14
0
2
Order By: Relevance
“…For now, antiviral activity is not as explored for clioquinol as the antifungal activity. Similarly, for nitroxoline, Zhang et al ( 2020 ) and Laurie et al ( 2018 ) proved that the drug has as good antiviral and antiparasitic action as Cherdtrakulkiat et al ( 2016 ) and Kudera et al ( 2020 ) proved its known antibacterial activity. Dealing with the antiviral activity of nitroxoline, the result found by Zhang et al ( 2020 ) (EC 50 = 2.482 μM) against Japanese encephalitis virus (JEV) was promising as the result found by Olaleye et al ( 2021 ) for antiviral activity of clioquinol (IC 50 = 12.62 µM) against SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…For now, antiviral activity is not as explored for clioquinol as the antifungal activity. Similarly, for nitroxoline, Zhang et al ( 2020 ) and Laurie et al ( 2018 ) proved that the drug has as good antiviral and antiparasitic action as Cherdtrakulkiat et al ( 2016 ) and Kudera et al ( 2020 ) proved its known antibacterial activity. Dealing with the antiviral activity of nitroxoline, the result found by Zhang et al ( 2020 ) (EC 50 = 2.482 μM) against Japanese encephalitis virus (JEV) was promising as the result found by Olaleye et al ( 2021 ) for antiviral activity of clioquinol (IC 50 = 12.62 µM) against SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 97%
“…Unlike clioquinol, the activity best reported in the literature for nitroxoline was antibacterial activity, consisting of 14 articles from Pubmed, Embase, and Web of Science databases. However, similar to what occurred for the antifungal activity of clioquinol, the articles dealing with the antibacterial activity of nitroxoline are divided into articles focused on one or a few microorganisms, such as the one by Ancuta et al ( 2016 ), the one by Fuchs et al ( 2019 ) and that of Kresken and Körber-Irrgang ( 2014 ), as well as articles investigating the spectrum of action of the drug against several microorganisms, such as that of Cherdtrakulkiat et al ( 2016 ) and Kudera et al ( 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[Euphorbiaceae]) was higher than the activities revealed against different strains of bifidobacteria. In our previous study, we also reported that 8-hydroxyquinoline exerts selective in vitro antiproliferative activity against some intestinal cancer cell lines with a comparably lower effect on normal cells (Kudera et al, 2020). Quinoline alkaloids, such as camptothecin extracted from the bark of Camptotheca acuminata Decne.…”
Section: Introductionmentioning
confidence: 94%
“…In the search for selective agents that are capable of treating bacterial diarrhoea without affecting the host intestinal microbiota, L. Kokoska et al [18] investigated ten phytochemicals and their synthetic analogues (berberine, bismuth subsalicylate, ferron, 8-hydroxyquinoline, chloroxine, nitroxoline, salicylic acid, sanguinarine, tannic acid, and zinc pyrithione) in vitro and compared the results with six commercial antibiotics (ceftriaxone, ciprofloxacin, chloramphenicol, metronidazole, tetracycline, and vancomycin) against 21 intestinal pathogenic/probiotic (e.g., Salmonella spp. and bifidobacteria) bacterial strains and three intestinal cancer/normal (Caco-2, HT29, and FHs 74 Int) cell lines.…”
mentioning
confidence: 99%